Analgesic effects of Iranian oak extract (Quercus brantii) mediated by the opioid system under stressful situations in female mice: Opioid system mediates the analgesia induced by Iranian Oak extract - Pourkhosravi, Hossein; Kesmati, Mahnaz; Torabi, Mozhgan (Iranian Journal of Pharmaceutical Sciences, 2025)
This study investigated the mechanism of the analgesic effect of oak fruit extract in interference with an opioidergic system in female mice under acute stress induction. Adult female mice were divided into groups of control, oak extract 1, 10, and 100 mg/kg, morphine and naloxone 1 mg/kg, morphine or naloxone/oak 1 and 100 mg/kg, restraint stress (60 minutes), stress/ naloxone 1 mg/kg and stress/ naloxone/oak 1 or 100 mg/kg. All mice were co-cycled before the beginning of the study; the formalin test induced inflammatory pain. Components were injected after stress induction, and formalin tests were done 30 minutes after injections. Oak fruit hydroalcoholic extract was obtained using the maceration method. Serum total oxidant status (TOS) and total antioxidant capacity (TAC) were measured. Oak extract 100 mg/kg induced analgesia in the acute phase of pain, and all doses induced analgesia in the chronic phase. Morphine improved the analgesic effect of oak extract 100 mg/kg in the acute phase. Naloxone in the stressed mice induced analgesia in the acute phase and improved the analgesic effect of Oak 100 mg/kg in the chronic phase. In the stressed mice, the TOS level was increased by the oak 1 mg/kg and decreased by the oak 100 mg/kg. Probably part of the analgesic effect of oak is due to the activity of the opioid system in acute stress situations. In addition, the change in the ratio of oxidant/antioxidant compounds in this process indicates that the mechanism of action of oak fruit in modulating pain and inflammation is multifactorial.